Influence of blasting charges and delays on the energy consumption of mechanical crushing - Dragano,Maria Antonietta (2019)
Abstract This article deals with a study performed at the Experimental Mine of the Research Center of Responsible Mining of the University of São Paulo, to examine the correlations between geological environment, blasting parameters and energy consumption in the primary crushing phase. The research is designed to appreciate the relationships between the energy provided for size reduction and the resistances to size reduction. For this purpose, Key Performance Indicators (KPIs) are used to describe the possible improvements on the energy consumption due to crushing. Four blast tests were performed: for each blast, KPIs were recorded regarding the blast design, the particle size distribution, the real power energy consumption at the primary crushing unit and its rate of utilization. The results show that energy consumption at the primary crusher is a sum of two components: energy directly involved in crushing the rock, and additional energy used for winning the inertial resistances of the moving parts of the crusher. We show how explosive energy and delay times influence the production of coarse fragments that jam the crusher, therefore influencing machinery stops and inertia loads related to putting the jaws back into movement.